Identifying the Barriers to Self-Wound Management in Singapore—A Preliminary Study in the Primary Healthcare Sector - Ling Jia Goh BHSc (Nursing), MHA, MClin Res; Xiaoli Zhu PostGd Dip Wound, MN, PhD Candidate (Journal of Patient Experience)
Singapore's growing elderly population faces a rising burden of chronic wounds. Studies have shown the beneficial effects of shared wound management where the patient actively manages their wound with guidance from their healthcare professionals. However, this concept faces challenges due to patient resistance. This study investigates barriers hindering patients’ participation in self-wound care. Addressing these barriers to aid the development of targeted strategies can increase the uptake of self-wound care. A locally validated survey was conducted among 328 patients in the polyclinics to assess their hesitancy toward self-wound care. A lower score on the scale indicated a high hesitation toward the concept of self-wound care. Forty-five percent of the participants expressed hesitation toward self-care. Strong family support emerged as a crucial factor in encouraging participation. Conversely, concerns about improper technique, missed diagnoses, and wound infection were prevalent. Logistic difficulties also influenced anxieties. Younger patients and those with higher education exhibited less apprehension. Educational interventions, tailored to address anxieties and empower patients with proper techniques, are critical. Fostering communication within families and examining the process of acquiring wound dressing materials are crucial in overcoming these barriers to self-wound care.